Challenges of implementing AI marketing in e-commerce businesses in North Macedonia - Gjorgjina Sherovska (Mednarodno Inovativno Poslovanje)
This study delves into the complex landscape of e-commerce in North Macedonia, focusing on the challenges encountered by e-commerce businesses in the implementation of Artificial Intelligence (AI) marketing strategies. Through a comprehensive survey involving 115 active participants in the e-commerce sector, the research identifies and navigates the obstacles that impede the smooth integration of AI marketing in the region. The primary goal is to meticulously investigate the distinctive challenges confronted by North Macedonian e-commerce enterprises when adopting AI marketing. The study sheds light on intricacies related to technological integration, resource limitations, and the dynamic interplay between consumer expectations and AI-driven marketing initiatives. Despite these challenges, there is a notable expression of satisfaction, indicating the resilience and adaptability of businesses. The examination of AI implementation stages, challenges faced, and subsequent measures taken provides valuable insights into the evolving relationship between AI technologies and e-commerce practices. This knowledge can guide e-commerce businesses in North Macedonia and similar regions in successfully integrating AI into their marketing strategies. This study not only illuminates the current state of AI marketing integration in North Macedonian e-commerce but also explores the readiness of organizations for AI marketing strategies. It highlights a prevalent inclination towards proactive engagement, offering original insights into the practical realities and future prospects of AI marketing in the e-commerce sector.